Spectroscopy properties of Er3+ ion doped ZnO-Al2O3-BaO-B2O3 glass for photonic application. (2018) - Yuliantini, L.; Djamal, M.; Hidayat, R.; Boonin, K.; Kaewkhao, J.
Abstract: The physical, optical and luminescence properties of Er 3+ ion doped borate glass have been developed by melt-quenching technique. The density and molar volume of glass medium increased with increasing Er2 O3 concentration due to the enhancement of non-bridging oxygen intensity in the glass structure. The quenching concentration effect was obtained at 2.0 mol% Er2 O3 . The strongest absorption occurred at 524 nm ( 4 I15 → 2 H1 ). The emission spectra excited by λex = 524 nm showed the 4 I13/2 → 4 I15/2 transition centered at 1534 nm. From presented data, the borate glass doped Er 3+ ion is a potential material to be developed for telecommunication and an optical amplifier.